2020
DOI: 10.1111/are.14558
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fishmeal with corn gluten meal, pea protein isolate and their mixture in diet of black sea bream ( Acanthopagrus schlegelii ) juveniles: Effects on growth performance, feed utilization and haematological parameters

Abstract: Corn gluten meal (CGM), pea protein isolate (PPI) and their mixture (CPP, 1:1 ratio) were evaluated as fishmeal (FM) alternatives in black sea bream (Acanthopagrus schlegelii) juveniles (9.02 ± 0.12 g). A FM diet was designed as control, and other six diets had 20% and 40% FM protein replaced by CGM, PPI and CPP, respectively, with the supplementation of crystalline methionine, arginine and lysine. After the 8‐week feeding trial, significantly lower weight gain was found in fish fed the 40% CGM diet (p < .05),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The present study showed that amino acids, including Met, Cys, Tyr and Pro contents, increased and in all ESM inclusive groups, especially in amino acid supplemented groups (E+A and E+AB). Phe content increased in the other four groups compared with the FM diet, which is consistent with black sea bream (A. schlegelii) following the replacement of fish meal with a mixture of phytogenic protein (Wang et al, 2020). These results indicated the positive role of supplemental amino acids in enhancing protein anabolism or inhibiting protein catabolism.…”
Section: Fillet Amino Acid Compositionsupporting
confidence: 75%
“…The present study showed that amino acids, including Met, Cys, Tyr and Pro contents, increased and in all ESM inclusive groups, especially in amino acid supplemented groups (E+A and E+AB). Phe content increased in the other four groups compared with the FM diet, which is consistent with black sea bream (A. schlegelii) following the replacement of fish meal with a mixture of phytogenic protein (Wang et al, 2020). These results indicated the positive role of supplemental amino acids in enhancing protein anabolism or inhibiting protein catabolism.…”
Section: Fillet Amino Acid Compositionsupporting
confidence: 75%
“…16 to analyze the statistical difference one-way ANOVA, followed by the Duncan test [61]. In addition, two-way ANOVA was used to determine the effects of the protein level, carbon source, and their interaction [62]. Significance was set as p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with our previous studies on turbot and shrimp demonstrating the great variation on free AA after a higher percentage of FM was replaced by alternative proteins [ 48 , 49 ]. We envisaged that the changes of free AA profile after 60% FM replaced by CSM might be partially due to the unbalanced AA composition of higher CSM containing diets [ 50 , 51 ]. A lower level of free AA in muscle not only decreased the bricks for protein synthesis and antioxidative capacity but also disordered the glycolipid metabolism [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%